Kajian Sistem Agribisnis Kopi Organik Di Daerah Pegunungan Gayo - Romano, Romano (Jurnal Aplikasi Manajemen, 2009)
Coffee is a represent best agribusiness commodity at Aceh Tengah and Bener Meriah. Have many strive to increase value added at organic coffee product in this area. Integration from agro production subsystem, processing and marketing of coffee with LTA77 project have sharing to improve coffee production, from extensification/intencification, and to increase product quality of organic coffee, formulated strategic promotion efforts of Gayo trade mark (Gayo Mountaint Coffee). This effort have improved coffee exporting value. This research aim to conduct study at agribusiness organic coffee system in this area. Result of research indicate that all of subsystem of agribusiness (agro production, processing subsystem and commercial agro marketing) of organic copy are prospective. Obtained advantage entirely bigger than level of interest at commercial bank. Competition level at all of lini enough tighten, so that only by upgrading can be obtained by larger value added. Quality of organic coffee can be improved by developing local pre-eminent variety (arabika), conservation of intensive crop, culture technique, appropriate specific huller, quality of row material at hulling, way of drier and packaging.